Clinical Features and Genetic Analysis of Children With Hyperekplexia in Korea. (January 2013) - Lee, Cha Gon; Kwon, Min-Jung; Yu, Hee Joon; Nam, Sook Hyun; Lee, Jeehun; Ki, Chang-Seok; Lee, Munhyang
Hyperekplexia is a rare inherited neurologic disorder that is characterized by hypertonia and an exaggerated startle response to sudden external stimuli. Until now, 5 genes are known to be associated with hyperekplexia: GLRA1, SLC6A5, GLRB, GPHN, and ARHGEF9 . In this report, we performed a clinical and genetic analysis of 4 Korean children with hyperekplexia. Two patients had typical clinical manifestations of hyperekplexia that initially were misdiagnosed as epilepsy. Direct sequencing of the GLRB and GLRA1 genes revealed 2 novel mutations, GLRB c.298-1G>A and c.1028C>T (p.S343F), in patient 1 and 1 novel mutation, GLRA1 c.895C>T (p.R299X), in patient 2. The other 2 familial cases, patients 3 and 4, exhibited startle responses, which appeared at the age of 1 year, and had global developmental delay. Those patients showed negative results for the 5 genes.